2013
DOI: 10.1371/journal.pone.0080933
|View full text |Cite|
|
Sign up to set email alerts
|

Astrocytes Directly Influence Tumor Cell Invasion and Metastasis In Vivo

Abstract: Brain metastasis is a defining component of tumor pathophysiology, and the underlying mechanisms responsible for this phenomenon are not well understood. Current dogma is that tumor cells stimulate and activate astrocytes, and this mutual relationship is critical for tumor cell sustenance in the brain. Here, we provide evidence that primary rat neonatal and adult astrocytes secrete factors that proactively induced human lung and breast tumor cell invasion and metastasis capabilities. Among which, tumor invasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
73
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 37 publications
6
73
0
Order By: Relevance
“…As discussed earlier, we and others have identified astrocyte secreted MMP-2, MMP-9, and MMP-1 to promote tumor progression, and blocking them with broad spectrum MMP inhibitors does influence tumor metastasis in pre-clinical models [95,96,[165][166][167]. Interestingly, MMP-1 was one of 21 MMPs that showed clinical significance in regards to breast cancer brain metastasis, and expression analysis of brain-seeking triple negative breast cancer clonal cells confirm MMP-1 and MMP-9 as potential targets [133,168].…”
Section: Enzyme Targetssupporting
confidence: 51%
See 2 more Smart Citations
“…As discussed earlier, we and others have identified astrocyte secreted MMP-2, MMP-9, and MMP-1 to promote tumor progression, and blocking them with broad spectrum MMP inhibitors does influence tumor metastasis in pre-clinical models [95,96,[165][166][167]. Interestingly, MMP-1 was one of 21 MMPs that showed clinical significance in regards to breast cancer brain metastasis, and expression analysis of brain-seeking triple negative breast cancer clonal cells confirm MMP-1 and MMP-9 as potential targets [133,168].…”
Section: Enzyme Targetssupporting
confidence: 51%
“…The expression of MMP-9 was up-regulated in reactive astrocytes, which was involved in the brain metastases of MDA-MB-435 cells [56]. Moreover, both MMP-2 and -9 secreted by astrocytes contribute to breast cancer MDA-MB-231 cell invasion and brain metastases [95]. In addition to secreting MMPs themselves, astrocytes can also induce tumor cells to secrete MMPs, as shown by Mendes et al (2007), where they found breast cancer cells to secrete significantly more MMP-2 in the presence of astrocyte conditioned media, aiding metastasis to the brain [96].…”
Section: Extracellular Matrix (Ecm) Proteins and Degradative Enzymesmentioning
confidence: 96%
See 1 more Smart Citation
“…During metastasis, tumor cells encounter many heterogeneous microenvironments containing an array of biochemical and physical cues (2), both of which regulate the migration, mechanobiology, and signaling mechanisms used by tumor cells to navigate these environments (3). It has been shown that astrocytes in the brain microenvironment promote brain metastasis and facilitate tumor cell invasion (4)(5)(6)(7)(8). We hypothesize that astrocyte-secreted biochemical cues regulate the morphology and migration of metastatic breast tumor cells and that this effect depends on the astrocyte activation state, as well as the mechanical microenvironment of the tumor cells.…”
mentioning
confidence: 99%
“…Secretion of MMPs by astrocytes does not necessarily require 2-way communication between tumor cells and astrocytes (5) and thus could be a part of the 1-way paracrine signaling of astrocytes to tumor cells that we explored in this study. MMPs are secreted by various cell types including both astrocytes and tumor cells, function to degrade the extracellular matrix, and are known to promote tumor cell splitting from a primary tumor, intravasation into the vasculature, and extravasation across capillary endothelial cells and the BBB (13).…”
mentioning
confidence: 99%